Integrated Analysis of Interglacial Climate Dynamics (INTERDYNAMIC) - Schulz, Michael; Paul, Andre (SpringerBriefs in Earth System Sciences, 2015)
The work addresses the following questions in the context of interglacial climate dynamics: (i) What are the amplitudes of natural climate variations on timescales of several years to millennia? (ii) Do abrupt changes in the large-scale circulation of the Atlantic Ocean occur in interglacials? (iii) Which biogeochemical feedback mechanisms control the natural limits of atmospheric concentrations of greenhouse gases and aerosols? (iv) Which linkages exist between climate and pre-industrial cultures? The work is based on an integrated approach in paleoclimate research, in which all available paleoclimate archives (terrestrial and marine as well as ice cores) are combined in order to yield a comprehensive and quantitative analysis of global environmental variations. Moreover, through a close linkage be-tween paleoclimate reconstructions and results from Earth-system models detailed insights into the dynamics of climate variations are gained.